Peculiarities of forming phonetic awareness in the introductory communicative corrective course - В. М. Гутник (Іноземні мови, 2016)
Abstract. Introduction. When it comes to college students, phonetic competence is formed at the beginner stage of learning a foreign language. Traditionally, language majors are offered in the Introductory Communicative Corrective Course during their freshman year. Phonetic competence includes phonetic skills, phonetic knowledge and phonetic awareness. The effectiveness of forming phonetic competence depends on how well its components are developed. What makes the formation of phonetic competence especially challenging is the filtering influence of the students’ mother tongue and a misconception of the approximation principle, which is typical of grade teachers. Students usually display deformed and fossilized phonetic skills, lack of differential sensitivity to phonetic units of different levels, as well as insufficient phonetic awareness. Purpose. The purpose of this research is defining the concept of phonetic awareness, its nature, peculiarities and its influence on the process of forming phonetic competence. The author offers a set of phonetic exercises geared toward forming phonetic competence. Methods. A detailed study of scientific resources devoted to the study of forming phonetic competence and its components enabled us to use all the existing approaches to the description of this phenomenon as part of the communicative competence of a foreign language. Author’s experience in teaching German at the college level and the awareness of all the challenges related to it allowed to come up with a set of exercises for developing phonetic competence as a whole and for phonetic awareness in particular. Results. The exercises suggested for developing phonetic awareness as a component of phonetic competence are based on the existing tenets of psycholinguistics, methodology of teaching, and didactics. The exercises can be used both in the Introductory Communicative Corrective Course for future teachers of German and as a separate series of drills geared toward the improvement of phonetic competence and its components.